Histomorphometric Study of the Glomeruli of the Kidney in Bangladeshi Population - Johora, Fatema; Nurunnabi, Abu Sadat Mohammad; Shahriah, Sunjida; Ahmed, Rukshana; Ara, Shamim (Journal of Bangladesh Society of Physiologist, 2015)
Background: Controversies still prevail on glomerular changes of kidney whether due to normal aging or its association with diseases Objective: The aim of the present study was to see the variation in number and size of the glomeruli of kidney with increasing age in a Bangladeshi population based on autopsy. Methods: This cross-sectional, descriptive study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from July 2008 to June 2009, based on collection of 140 post mortem human kidneys collected from 70 unclaimed dead bodies from the morgue. All the samples were divided into three age-groups: 10-19 years, 20-39 years and 40-59 years. Histological slides were prepared by using routine Harris Haematoxylin and Eosin (H & E) stain. The number of glomeruli was measured by point counting technique, while the size (diameter) was measured by using ocular and stage micrometer. Results: The mean ± SE number of glomeruli per sq. mm found in the right and left kidney were 8.45±0.52 and 8.67±0.80 in group 10-19 years, 9.90±0.42 and 9.92±0.47 in 20-39 years, and 8.52±0.18 and 8.55±0.16 in 40-59 years respectively. Besides, the size (mean ± SE diameter) of glomeruli was found in the right and left kidney were 43.96±3.01ìm and 143.92±2.90ìm in group 10-19 years, 153.69±5.18ìm and 153.61±5.24ìm in 20-39 years, and 140.48±0.95ìm and 140.78±0.88ìm in 40-59 years respectively. Conclusion: No difference was found in number and size of glomeruli between right and left kidney in any group. Similarly, no difference was also evident among different age groups. DOI: http://dx.doi.org/10.3329/jbsp.v9i1.22788 Bangladesh Soc Physiol. 2014, June; 9(1): 11-16